2020
DOI: 10.1021/acsinfecdis.9b00419
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Hidden Antibiotic Potential of Cannabis

Abstract: The spread of antimicrobial resistance continues to be a priority health concern worldwide, necessitating exploration of alternative therapies. Cannabis sativa has long been known to contain antibacterial cannabinoids, but their potential to address antibiotic resistance has only been superficially investigated. Here, we show that cannabinoids exhibit antibacterial activity against MRSA, inhibit its ability to form biofilms and eradicate pre-formed biofilms and stationary phase cells persistent to antibiotics.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
163
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(189 citation statements)
references
References 35 publications
(57 reference statements)
4
163
0
Order By: Relevance
“…Farha and co-workers evaluated several cannabinoid analogs against MRSA USA300 and E. coli [65]. Several common cannabinoids (35-43, 45, 47) demonstrated moderate to good activity; these results mostly align with previous studies (vide supra).…”
Section: Structure-activity Relationships Of Cannabinoidssupporting
confidence: 75%
“…Farha and co-workers evaluated several cannabinoid analogs against MRSA USA300 and E. coli [65]. Several common cannabinoids (35-43, 45, 47) demonstrated moderate to good activity; these results mostly align with previous studies (vide supra).…”
Section: Structure-activity Relationships Of Cannabinoidssupporting
confidence: 75%
“…In comparison to conventional antibiotics, CBG had a lower minimum inhibitory concentration than norfloxacin in 5 of the 6 strains tested, and was more potent than erythromycin, tetracycline, and oxacillin in at least one resistant strain (Appendino et al, 2008). Using a systemic S. aureus infection model in mice, Farha and coworkers showed that CBG was as effective at reducing colony forming units as vancomycin (Farha et al, 2020). This study also found that CBG was effective against gram-negative bacteria only when the outer membrane was first permeabilized, suggesting that the outer membrane of gram-negative bacteria presents a permeability problem for cannabinoids (Farha et al, 2020).…”
Section: Antibacterial Agentmentioning
confidence: 99%
“…Using a systemic S. aureus infection model in mice, Farha and coworkers showed that CBG was as effective at reducing colony forming units as vancomycin (Farha et al, 2020). This study also found that CBG was effective against gram-negative bacteria only when the outer membrane was first permeabilized, suggesting that the outer membrane of gram-negative bacteria presents a permeability problem for cannabinoids (Farha et al, 2020). Using in silico modeling, Pinzi and colleagues found that CBG acts as an inhibitor of enoyl acyl carrier protein reductase (InhA), and they verified their model with in vitro testing and found CBG inhibits enoyl acyl carrier with an IC 50 value in the low micromolar range (Pinzi et al, 2019).…”
Section: Antibacterial Agentmentioning
confidence: 99%
“…The exposure of (CBC) (19) to sunlight leads to a [2 + 2]-photocycloaddition forming cannabicyclol (CBL) (21) [48]. Finally, there is a very diverse group of miscellaneous-type cannabinoids, which can be isolated from Cannabis sativa in small amounts such as (−)-exo-trans-tetrahydrocannabinol (exo-THC) (22) or the dimeric cannabisol (23). Furthermore, less abundant in Cannabis sativa are phytocannabinoids presenting a C19 and C22 terpenophenolic skeleton, such as cannabidivarin (CBDV) (12) or (−)-∆ 9 -trans-tetrahydrocannabivarin (∆ 9 -THCV) (3) (Figure 1), which is regarded to different biosynthetic precursors [49][50][51].…”
Section: Structures Abundance and Biosynthetic Origin Of Natural Camentioning
confidence: 99%
“…Natural products have always been a rich source for the identification of antimicrobial drug candidates; thus, researchers have started to reinvestigate long known natural product-based drugs in order to provide solutions to the current antibiotic crisis [15][16][17][18][19][20][21][22]. Interestingly, different phytocannabinoids, natural product constituents of the extracts of the plant Cannabis sativa, which have so far mainly been associated with intoxication effects upon recreational usage and medical applications far beyond the treatment of infections, have been reported to show antibacterial activity against several Gram-positive bacterial pathogens, including MRSA [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%